Serving two masters: Role expectation enactment and anticipated careers of service professionals - Barbulescu, Roxana; Jonczyk Sédès, Claudia; Galunic, Charles; Bensaou, Ben (My University, 2017)
While only a small minority of professionals joining a professional service firm (PSF) make it to partnership, we know little about how the individuals themselves navigate that system - in particular, how they decide to stay and pursue the partnership track, what makes them leave the firm, and whether and when these decisions may co-exist. This study adopts a role expectations enactment lens to examine the strategies that individuals engage in to mange their careers, both those who seek to "make it" within the firm and those who may prepare their exit. Building on in-depth interviews with 60 pre-partnership professionals in accounting, consulting, and law, we uncover four anticipated career paths - partner-track, client-track, off-track and wait-and-see - and corresponding systematic variations in the ways that professionals enact their role with respect to partners and clients. We find that individual career agency is embedded in the proximate social structures that circumsribe professionals role expectation enactment. In particular, findings highlight how partner-client portfolio constellations impinge on the ability to engage in specific forms of role enactment beyond what both the traditional PSF literature and the proteancareer lens would lead us to expect.
, 2017
Keywords: Role enactment; Careers; Professional service firms